Disability-adjusted life years and the trends of the burden of colorectal cancer: a population-based study in Shanghai, China during 2002 to 2016. Issue 24 (20th December 2022) - Zhong, Wei; Chen, Liping; Li, Xiaopan; Chen, Yichen; Zhang, Yao; Guo, Canjie; Shen, Yufeng; Chen, Huimin
Abstract: Background: Colorectal cancer (CRC) still ranks the top in morbidity and mortality of cancers worldwide, posing a huge threat and burden to the society. We aimed to determine the age-standardized incidence, mortality, and disability-adjusted life years (DALYs) of CRC and explore potential changes in the temporal trends of the CRC burden in Shanghai during 2002 to 2016. Methods: The cancer statistics and demographics were obtained from the Cancer Registry and the Statistics Bureau of Pudong New Area, respectively. Data from 2002 to 2016 were included and analyzed retrospectively. DALYs were calculated using DisMod and the age-standardized rates (ASRs) were obtained according to Segi world standard population. Joinpoint regression was used to measure the trends in CRC incidence and to estimate the annual percent change. Results: The increasing trend of CRC ASR incidence halted after 2014, coinciding with the introduction of the Shanghai CRC screening program. The ASRs of mortality and DALYs increased, at 0.42% ( P  < 0.05) and 4.07% ( P  < 0.001) per year, respectively, which were mainly driven by men and individuals aged above the CRC screening program target. Conclusions: The disease burden of CRC in Shanghai remains serious, especially among men, and individuals aged >74 years. The benefits of the screening program have been partially proven by the ASRs of CRC incidence, providing important insights into better and wider application of screening programs.